Wastewater Treatment of Tofu Industry Using Microbial Fuel Cell Method - Anwar Ma'ruf; Tia Anggraeni (Research in Chemical Engineering, 2024)
Microbial Fuel Cell (MFC) is a system for generating electrical energy by utilizing the interaction of bacteria with substrate. MFC generates electricity by oxidizing organic matter with the help of microbes. In this study, the substrate is tofu wastewater and cow rumen bacteria. The MFC used is a dual chamber equipped with a TiO2 clay ceramic membrane. This study aimed to determine the production of electrical energy from tofu liquid waste substrate using MFC technology with the addition of nutrients in the form of urea and bacteria from the cow's rumen. The variation of the ratio of tofu liquid waste used is 20%. 40%, 60%, 80% and 100%. While the variations in the concentration of urea used were 1 - 5 grams. The results show that the greater the variation in the ratio of tofu liquid waste, the greater the energy potential. The highest average electric power is 381 volts from the 100% tofu liquid waste ratio. In addition, the greater the urea concentration the more it produces a large energy potential. The highest average electric power is 421 volts from 5 grams of urea concentration. The TiO2 clay ceramic membrane in the MFC system was able to reduce the TSS and TDS values ​​of tofu liquid waste. The highest percentage decrease for TSS is 37% and for TDS is 25% at the variation of the ratio of tofu liquid waste 100%.